Hubungan Rasio CT dan Ekspresi Gen E dengan Kejadian Gagal Napas pada Pasien Covid-19 Rawat Inap di RS X - Dika Rifky Fernanda; Lelly Yuniarti (Jurnal Riset Kedokteran, 2022)
Abstract. Introduction: Corona virus disease 2019 (COVID-19) is a new disease that causes millions of deaths worldwide. The majority of deaths are due to pulmonary degeneration leading to respiratory failure. The gold standard for COVID-19 diagnostics is the examination of the nucleic acid of the SARS-CoV-2 virus using RT-PCR which produces CT values for the SARS-CoV-2 gene target and internal control (CT). One of the target genes that is often examined in COVID-19 examination is gene E. This study aims to analyze the relationship between the CT IC/CT gene E ratio and the relative expression of the SARS-CoV-2 E gene with the incidence of respiratory failure. Methods: This study is a cross sectional study conducted at X General Hospital on 196 patients. Data obtained from medical records in the form of patient characteristics and PCR examination results from the laboratory. Relative gene expression was calculated using the livak method (2-ΔΔCT). The CT ratio was calculated by comparing the internal control CT with the CT gene E. The relationship of gene relative expression and CT ratio with the incidence of respiratory failure was analyzed using thestatistic unpaired t-test at 95% confidence level. Results: The results showed that the characteristics of COVID-19 patients were more males, aged 41-60 and 40 of the total patients experienced pulmonary distress. The unpaired t-test showed that there was no relationship between the CT IC/CT gene E ratio and the relative expression of the SARS-CoV-2 gene E and the incidence of respiratory failure, with P values (P=0.2083) and (P=0,8018). Conclusion: The conclusion of this study is that there is no relationship between the ratio of internal control CT/CT of the SARS-CoV-2 gene and the relative expression level of the SARS-CoV-2 E gene with the incidence of respiratory failure in confirmed COVID-19 patients hospitalized at Hospital X. There are several factors that influence the incidence of respiratory failure in addition to comorbidities such as age and gender. Abstrak. Pendahuluan: Corona virus disease 2019 (COVID-19) adalah penyakit baru yang menyebabkan jutaan kematian di seluruh dunia. Mayoritas kematian disebabkan oleh perburukan paru yang berujung pada gagal napas. Standar baku emas diagnostik COVID-19 adalah pemeriksaan asam nukleat virus SARS-CoV-2 dengan menggunakan RT-PCR yang menghasilkan nilai CT target gen SARS-CoV-2 dan internal control (CT). Salah satu gen target yang sering diperiksa pada pemeriksaan COVID-19 adalah gen E. Penelitian ini bertujuan untuk menganalisis hubungan rasio CT IC/CT gen E dan ekspresi relatif gen E SARS-CoV-2 dengan kejadian gagal napas. Metode: Penelitian ini merupakan penelitian cross sectional yang dilakukan di RS X pada 196 pasien. Data diperoleh dari medical record berupa karakteristik pasien dan hasil pemeriksaan PCR dari laboratorium. Ekspresi gen relatif dihitung dengan menggunakan metode livak (2-ΔΔCT). Rasio CT dihitung dengan membandingkan CT internal control dengan CT gen E. Hubungan ekspresi relatif gen dan rasio CT dengan kejadian gagal napas dianalisis menggunakan uji statistik unpaired t-test pada tingkat kepercayaan 95%. Hasil: Hasil penelitian didapatkan karakteristik pasien COVID-19 lebih banyak laki-laki, usia 41−60 dan 40 orang dari total pasien mengalami pulmonary distress. Uji unpaired t-test menujukan tidak terdapat hubungan antara rasio CT IC/CT gen E dan ekspresi relatif gen E SARS-CoV-2 dengan kejadian gagal napas, dengan nilai P berturut-turut P=0,2083 dan P=0,8018. Kesimpulan: Kesimpulan penelitian ini adalah tidak terdapat hubungan antara rasio CT internal control/CT gen E SARS-CoV-2 dan tingkat ekspresi relatif gen E SARS-CoV-2 dengan kejadian gagal napas pada pasien terkonfirmasi COVID-19 yang dirawat inap di RS X. Terdapat beberapa faktor yang memengaruhi kejadian gagal napas selain komorbid seperti usia dan jenis kelamin.